Determinant Factors of Stress in Caregivers of Patients With Schizophrenia: Cross-Sectional Study - Isymiarni Syarif; Hasnawati Amqam; Saidah Syamsuddin; Veni Hadju; Syamsiar Russeng; Yusran Amir (JMIR Formative Research)
Abstract BackgroundCaregivers of individuals with schizophrenia face ongoing psychological and emotional burdens due to the chronic and relapsing nature of the disorder and the complexity of caregiving. Prolonged exposure to caregiving stress characterized by emotional exhaustion, role overload, and lack of social support has been consistently associated with poor mental health outcomes among caregivers, including depression and anxiety. ObjectiveThis study aimed to assess stress levels among caregivers of patients with schizophrenia and identify the key determinants of caregiver stress. MethodsThis study used a cross-sectional survey that was conducted between June and August 2024 at the Labakkang District Health Center, South Sulawesi, Indonesia. A total of 110 female caregivers participated in the study. Data were collected using validated questionnaires to measure stress levels and related factors. Statistical analyses included chi-square tests to identify associations and partial least squares structural equation modeling to examine the strength and direction of relationships between variables. ResultsThis study included 110 female caregivers of individuals with schizophrenia. The majority were early older people (48/110, 44%), had a basic level of education (elementary to junior high school; 45/110, 46%), were unemployed (83/110, 75%), and had been providing care for more than 10 years (42/110, 38%). A total of 58 of 110 (53%) caregivers experienced mild levels of stress, while 63 of 110 (57%) caregivers reported a moderate caregiving burden. Additionally, 64 of 110 (58%) caregivers reported challenges related to patient treatment nonadherence, and 58 of 110 (53%) caregivers experienced low levels of social stigma. Most caregivers (69/110, 63%) adopted adaptive coping strategies; however, more than half reported low levels of knowledge (59/110, 54%) and limited access to health information (73/110, 66%). The chi-square analysis identified several statistically significant associations with stress: age (PPPPPPPrrrr ConclusionsThese findings underscore the critical need for targeted interventions that enhance social support networks, reduce stigma, and strengthen caregivers’ coping capacities. Strengthening these dimensions is essential to mitigating the psychological toll of caregiving and sustaining caregivers’ functional well-being. Evidence increasingly supports that empowering caregivers through structured support systems and educational initiatives can substantially alleviate stress-related burdens and improve care continuity for individuals with schizophrenia.